Fish manuals 1 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Fish manuals Fermented fish in Africa is a report based on surveys carried out in eight West African countries. the Sudan and Uganda to identify the various types of fermented fishery products, their processing characteristics and economic...